Melatonin‐mediated inhibition of Cav3.2 T‐type Ca2+ channels induces sensory neuronal hypoexcitability through the novel protein kinase C‐eta isoform. Issue 4 (8th March 2018) - Zhang, Yuan; Ji, Heyi; Wang, Jiangong; Sun, Yufang; Qian, Zhiyuan; Jiang, Xinghong; Snutch, Terrance P.; Sun, Yangang; Tao, Jin
Abstract: Recent studies implicate melatonin in the antinociceptive activity of sensory neurons. However, the underlying mechanisms are still largely unknown. Here, we identify a critical role of melatonin in functionally regulating Cav3.2 T‐type Ca 2+ channels (T‐type channel) in trigeminal ganglion (TG) neurons. Melatonin inhibited T‐type channels in small TG neurons via the melatonin receptor 2 (MT2 receptor) and a pertussis toxin‐sensitive G‐protein pathway. Immunoprecipitation analyses revealed that the intracellular subunit of the MT2 receptor coprecipitated with Gαo . Both shRNA‐mediated knockdown of Gαo and intracellular application of QEHA peptide abolished the inhibitory effects of melatonin. Protein kinase C (PKC) antagonists abolished the melatonin‐induced T‐type channel response, whereas inhibition of conventional PKC isoforms elicited no effect. Furthermore, application of melatonin increased membrane abundance of PKC‐eta (PKCη ) while antagonism of PKCη or shRNA targeting PKCη prevented the melatonin‐mediated effects. In a heterologous expression system, activation of MT2 receptor strongly inhibited Cav3.2 T‐type channel currents but had no effect on Cav3.1 and Cav3.3 current amplitudes. The selective Cav3.2 response was PKCη dependent and was accompanied by a negative shift in the steady‐state inactivation curve. Furthermore, melatonin decreased the action potential firing rate of small TG neurons and attenuated the mechanical hypersensitivity in a mouse model of complete Freund's adjuvant‐induced inflammatory pain. These actions were inhibited by T‐type channel blockade. Together, our results demonstrated that melatonin inhibits Cav3.2 T‐type channel activity through the MT2 receptor coupled to novel Gβγ ‐mediated PKCη signaling, subsequently decreasing the membrane excitability of TG neurons and pain hypersensitivity in mice.